Design and Development of CBR, MPCR & DSCR Routing Energy- Efficient Protocols in WSNs -A Brief Overview about the Design Process - Hanumanthappa S. N.; Girish V. Attimarad (Journal of Power Electronics and Devices, 2020)
In this paper, a brief introduction to the improvisations in multipath cooperative routing protocols in WSNs using CBR, MPCR, and DSCR with a reduction in energy savings. To start with a brief introduction is given, followed by the applications of the WSNs and NS2 simulator along with the hardware & software tools for research purposes. Objectives & Outcomes are presented next followed by the motivation and the research problem statement. The list of contributory works is presented next followed by the conclusions. The paper gives brief introductory information about the chosen research work on the above-mentioned topic, which is a part of the thesis work extracted part.